Fire refugia under threat: How increasing pyrodiversity reduces species richness in unburned forests - Godoy, Ederson; Adorno, Bruno F.C.B.; da Silva, Bianca Dinis; Corrêa, Wellington; Barbosa, Vinícius Munhoz; Piratelli, Augusto João; Ribeiro, Milton Cezar [UNESP]; Hasui, Érica (Elsevier, 2025)
Recent research has emphasized the spatial and temporal variability of fire dynamics, which can enhance landscape heterogeneity by creating a mosaic of forest patches in different successional stages, a concept known as pyrodiversity. This study investigated the influence of pyrodiversity on bird guild species richness and assessed whether forest fire refugia moderate this relationship in fire-sensitive ecosystems. We conducted bird surveys across 15 landscapes in the southeastern Atlantic Forest of Brazil, chosen to represent a gradient of pyrodiversity and fire refugia. Using generalized linear mixed models, we analyzed the relationships between pyrodiversity, fire refugia, and species richness across bird guilds and microhabitats. Our findings revealed that frugivorous and nectarivorous, birds, along with species associated with canopy microhabitats, exhibited a strong negative correlation between pyrodiversity and species richness, particularly in unburned forests. The interaction between pyrodiversity and fire-affected habitats was significant, with species richness in unburned forests declining as pyrodiversity increased. This result highlights the vulnerability of species in unburned areas within highly pyrodiverse landscapes, where frequent fires disrupt ecological stability. There appears to be a threshold beyond which pyrodiversity becomes detrimental. In such landscapes, excessive pyrodiversity can lead to habitat simplification, negatively affecting species that rely on undisturbed vegetation for critical resources. Notably, 21 % of species richness, including threatened and endemic species, was found exclusively in unburned patches, underscoring the critical importance of these areas for biodiversity conservation. Effective conservation efforts must account for historical fire regimes to preserve the biodiversity and ecological integrity of tropical forests.
Keywords: Atlantic forest; Avian; Fire-sensitive ecosystem; Landscape heterogeneity; Time since fire; Trophic guild; Tropical forest; Wildfire